Nutrient and trace element concentrations influence greenhouse gas emissions from Malaysian tropical peatlands. (3rd November 2020) - Dhandapani, Selvakumar; Evers, Stephanie; Ritz, Karl; Sjögersten, Sofie
Abstract: Tropical peatlands are unique and globally important ecosystems for carbon storage that are generally considered nutrient poor. However, different nutrient and trace element concentrations in these complex ecosystems and their interactions with carbon emissions are largely unknown. The objective of this research was to explore the concentrations of macro‐ and micronutrients and othertrace elements in surface peats, and their relationship with greenhouse gas emissions in North Selangor peatlands subjected to different land use. All nutrient and trace element concentrations except chromium exhibited significant differences between sites. Most macronutrients and some micronutrients showed significant differences between seasons, typically with a reduction over time from wet to dry seasons, possibly due to leaching. CO2 emissions were positively related to organic matter content and manganese concentrations and negatively correlated with selenium. CH4 emissions were positively correlated with organic matter content, manganese, copper, barium, cobalt and aluminium, and negatively correlated with molybdenum, selenium, lithium and vanadium. This research has detected loss of essential nutrients over time, aiding to increase nutrient limitation in tropical peatlands due to drainage. The observed significant correlation between trace elements and greenhouse gas emissions strengthens the importance of including trace element analyses in understanding the biogeochemical functions of these understudied peatlands.